A biomechanical shoulder strain index based on stabilizing demand of shoulder joint. Issue 12 (2nd December 2018) - Chowdhury, Suman K.; Nimbarte, Ashish D.; Hsiao, Hongwei; Gopalakrishnan, Bhaskaran; Jaridi, Majid
Abstract: Work-related shoulder joint disorders contribute considerably to absenteeism in the workplace. To identify the tasks that are stressful to the shoulder joint, a strain index was formulated based on the concept of concavity compression—a shoulder stabilizing mechanism. The magnitude and direction of the shoulder joint reaction forces were used in formulating the strain index. A two phase experiment was conducted. In Phase 1, participants performed 30 different manual handling tasks. The tasks were categorized into low, medium and high strain tasks based on their strain index values. In Phase 2, out of the 30 tasks, repetitive exertions of three tasks (low, medium and high strain index values) were simulated using three external loads (0.91, 1.81 and 2.72 kg). The muscle activity data recorded from eight shoulder muscles showed that tasks with higher strain index values induced significantly greater activation and muscle fatigue than tasks with lower strain index values.Practitioner Summary: The strain index developed in this study is a conclusive estimation of the concavity compression required for shoulder joint stabilization. It can be used to identify the activities that may contribute to the risks of shoulder disorders. Abbreviation: BLS Bureau of the Labor Statistics